WhatsApp Usage Training in Marketing Home-Based Products for Benzo Amanah Cooperative Members Bandung Indonesia - Dwi Susanti; Mochamad Suyudi (Research Collaboration Community (RCC), 2020)
Currently, WhatsApp has become one of the categories of social networking that has been widely used by most people in Indonesia to share information. WhatsApp is believed not only to benefit online shops, retailers, restaurants, travel companies, and e-commerce but also to be one of the most effective tools in building a business brand. WhatsApp is not only in demand by men and women who are young entrepreneurs but also for communities who have a passion for developing businesses from home (home business). Community Service Activities that have been held on Tuesday, January 11, 2020, are carried out to socialize the use of the WhatsApp social network for members of the Bandung Indonesia Benzo Amanah Cooperative. The training was carried out using a 2-hour classical method in the form of making WhatsApp Group, delivering core material by expert speakers, and sharing experiences to further motivate Members of the Benzo Amanah Cooperative Bandung Indonesia to become a home mompreneur.